Effect of recycling process on metal ion release from orthodontic brackets at different periods - Shariati M; Soboti F; Amini F; Noshad Haghighi Z (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: Considering the application of recycled metallic brackets in orthodontic treatments and probably more resultant metal ion release, which can cause cytotoxic side effects, this study was set up to assess the effect of recycling process of orthodontic brackets on metal ion release."nMaterials and Methods: In this experimental study, 80 Discovery direct bond brackets (Dentarum, Germany) were divided into 2 groups, new and recycled brackets (n = 40), then each group was divided into two subgroups (one-week and 6-months subgroups) (n=20). The specimens were maintained in buffered solution of NaNHNo3"n(pH=7) at 37°C in an incubator. After periods of one week and 6 months immersion, 0.5 mL of each solution was analyzed by spectrophotometry for the quantity of released Nickel (Ni), Chromium (Cr), and Cobalt (Co) ions. The data were analyzed using two way ANOVA analysis."nResults: After one week, the quantity of Ni, Cr, and Co ions released from new brackets were 0.65, 1.4, and 0.75 (ppb), respectively. The values for recycled brackets were 142, 2.61, and, 1.43 (ppb). These findings indicated significant difference between two groups (P<0.001). After six months, the quantity of Ni, Cr, and Co ions released from new brackets were 1200, 3.4, and 2.4 (ppb) and from recycled brackets were 2330, 6.9, and 10.8 (ppb), which showed significant difference between two groups (P<0.001)."nConclusion: Application of recycled brackets in long fixed orthodontic treatments can lead to metal ion release, specifically Nickel. Thus, the use of recycled brackets in long orthodontic treatments is not recommended.